Video-Based Ice Breaker Game In The Department of Arabic Language Education - Taufiqurrochman, R.; Saeed Rana, Hafiz Ahmed (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Online and distance learning leads to reduced student motivation, boredom, and reduced levels of understanding. The solution to solve this problem is ice breaker-based video. In Arabic learning, ice breaker video content is not found much because ice breakers are usually practiced for offline learning. Therefore, ice breakers are required in videos for online learning by producing them in large quantities. This study aims to describe the results of a review of ice breaker-based videos that have been successfully designed by students in the Department of Arabic Language Education. It is a mixture of quantitative and qualitative approaches. With qualitative content analysis, it is known that students successfully produce Arabic-language ice breaker-based videos that are of good quality from the aspect of content, themes, and teaching materials for all levels of education, from children to adults. This video can be applied independently or under the guidance of a classroom teacher. The success of students in producing ice breaker-based videos is because the Arabic education curriculum has accommodated elective courses called Games, Songs, and Stories so that students are equipped with teaching skills and the ability to become content creators.